Thermal transport in suspended SWCNTs at high heat fluxes. (May 2017) - Liu, Jin-Hui; Xie, Huan-Huan; Hu, Yu-Dong; Zhang, Xing; Zhang, Ying-Ying
Highlights: We present an experimental study of temperature dependent thermal conductivities of SWCNTs using Micro-Raman spectroscopy. Spatially resolved temperature profiles in electrically heated individual short SWCNTs (60, 20 μm) were measured, with all the temperature profiles being highly symmetric parabolas. By comparing the temperature profiles with that predicated by Fourier's law, the results indicated that thermal transport in SWCNTs obeys Fourier's law at extremely high heat fluxes (1.4 × 10 11  W/m 2 ) above 300 K. Abstract: In recent years many reports have indicated that Fourier's heat conduction law is violated at size scales comparable to the mean free path of the heat transfer carriers or time scales of femtoseconds. Another open question is whether Fourier's heat conduction law still holds at extremely high heat fluxes. Here, we present an experimental study of temperature dependent thermal conductivities and spatially resolved temperature profiles in electrically heated single-walled carbon nanotubes (SWCNTs) using Raman spectroscopy. The experimental results yield evidence that thermal transport in SWCNTs obeys Fourier's empirical law at high heat fluxes ( q  = 1.4 × 10 11  W/m 2 ) above 300 K in vacuum.